Virtual reality-based training for radiopharmaceutical administration: development and educational effectiveness. - Akihiro Kakimoto; Daisuke Fujise; Shin Hasegawa; Yasuo Okuda; Yuto Ohta; Rikuha Tani; Miyu Niwase; Kazutoshi Miyamoto; Ryota Konishi; Masao Funahashi (PLoS ONE)
In Japan, task shifting and sharing are promoted to reduce the workload of physicians. Radiological technologists have been assigned new responsibilities, such as securing venous access for radiopharmaceutical administration. This study aimed to develop a prototype Virtual Reality (VR) training system that allows safe and repeatable training for radiological technologists. Additionally, the educational effectiveness of VR training was evaluated, and the concentration levels of the participants were assessed using multiple physiological indicators. Overall, 17 male and 12 female participants (mean age 20.1 ±  0.9 years) were enrolled in this study and classified into two groups-video-based and immersive VR system groups-both of which simulated radiopharmaceutical administration. Concentration and tension levels were evaluated using electroencephalography (EEG) data, salivary amylase levels, and mood assessments. The educational effectiveness was evaluated using a multiple-choice cognitive test. Compared with the resting levels, the alpha/beta ratio of EEG (indicating relaxed concentration) was significantly decreased by 19% in the video-based VR and increased by 40% in the immersive VR groups (both p < 0.05). No significant difference was observed in salivary amylase levels between the two groups. The cognitive test scores, increased by 2.0 and 3.4 points in the video-based VR and immersive VR groups, respectively; a significant difference was observed between both groups (p <  0.05). However, no correlation was found between the EEG ratio and test performance. Thus, immersive VR promotes a more relaxed and concentrated state and was found to have higher educational effectiveness than video-based VR. This suggests that participatory VR training may be more effective than observational VR training. Further research should explore the relationship between educational effectiveness and the evaluation of medical skills.